Drying kinetics of cocoa beans undergoing vacuum drying - Rahman, S M A; Chait, Y; Hawlader, Mohammad Nurul Alam (2012)
Cocoa bean is rich in polyphenol content that acts as an anti-oxidant, sensitive to high temperature. Therefore, vacuum drying method is proposed to maintain the polyphenol content during its preservation process. The main objective of this work is to determine the optimum drying temperature and vacuum pressure during drying of cocoa bean. Experiments were conducted by varying the temperature from 40OC to 60OC and pressure of vacuum oven from 0mmHg (atmospheric pressure) to 735mmHg (vacuum). The influence of various system parameters on drying kinetics and quality (in terms of color measurement) of the dried products has been investigated. Results revealed that cocoa beans dried at 50 OC and 735mmHg (vacuum) show higher drying kinetics, lower acidity and better color, while maintaining higher concentration of polyphone content of dried products. Compared with oven drying, conducted at 60OC, vacuum oven drying consistently shows better drying characteristics with good quality of dried products.